Real world radiation exposure in left atrial appendage occlusion device implantation performed in a high volume center. (14th October 2021) - Aslam, S; O'Grady, R; Casey, A; Kennedy, M; Hussein, H
Abstract: : Left atrial appendage occlusion (LAAO) is an established and effective treatment to reduce the risk of thromboembolic stroke derived from the LAA in patient with non valvular atrial fibrillation. Per-cutaneous closure of the LAA is typically guided by fluoroscopic and echocardiographic guidance. The purpose of our study is to ascertain real world radiation exposure during the LAAO performed in our institution and the interplay of different variables and patient characteristics. Our study retrospectively analyzed all consecutive LAAO procedures performed at our Tertiary level Teaching Hospital. Data was collected using Hospital electronic records and cardiac catherization laboratory records. A total of 261 patients who underwent LAAO were identified, 28% were female. Average age at the time of procedure was 77 years (range 54–93 years). Mean fluoroscopy time was 10.2 minutes (±7.0), average Radiation dose was 67 gy/cm 2 (±73). Interestingly, gy/cm 2 per minute of fluoroscopy averaged at 6.69 (±5.0). Subgroup analysis focused on the effect of Body mass index (BMI) on radiation dose. Since the recent introduction of a partial electronic health record system, BMI data was only available on 161 patients. The cohort with BMI <30 had a mean radiation dose of 57±62 gy/cm 2, whereas for BMI >30 mean dose was 96.8±68, p=0.0025 (95% CI (65 to 14)). Analysis by the four different device types (Watchman, Watchman Flx, Wavecrest and ACP) were used for LAAO, with highest number been watchman (n=189). Upon comparing the radiation exposure in our study cohort watchman device had the least Dose adjusted Product (DAP) at 62gy/cm 2 but the newer watchman flx (n=25) had slightly lower gy/cm 2 per minute of fluoroscopy time 6.58±3.41 versus 6.83±5.56. In addition, operator volume between our two implanters was assessed. Our highest volume operator implanted the majority of devices (n=235) whilst the Watchman Flx was predominantly implanted by our newer implanter (n=26). Despite the relatively modest numbers of the Watchman Flx, there was minimal difference in exposure time in favor of the more senior interventionist. In conclusion, LAAO in our center has encouraging radiation safety data, which is comparable to previously published data in internationally recognized high volume centers. Normal BMI patients had the least radiation exposure, with the dose increasing with rising BMI. Funding Acknowledgement: Type of funding sources: None.